Study of maternal and perinatal outcomes in twin pregnancies delivered at a tertiary centre hospital in Southern Rajasthan - Sekhasaria, Priyanka; Chundawat, Rama S.; Shivrayan, Suman; Agarwal, Akanksha; Jakhar, Balveer (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Twin pregnancy occurs when two babies are growing inside the uterus. The idea of twinning has fascinated people for as long as humans have been writing history. The primary concerns that arise during twin pregnancies include congenital malformations, birth trauma, birth asphyxia, intrauterine growth restriction (IUGR), premature birth, and low birth weight. The main factor that poses the highest risk is premature birth, which is mainly responsible for the higher chances of perinatal death, neonatal illness, and long-term problems in twins. Methods: A total of 48 twin pregnant women with at least 28 weeks of gestation were observed during their hospitalization at Pacific Medical College and attached hospital in Udaipur, Rajasthan, from July 2021 to June 2024 (over a span of 3 years). Results: Among the 2980 deliveries conducted at our facility, 48 instances of twin pregnancies were analysed in this research. 1.61% of pregnancies were twins. Most research subjects were aged between 20 and 29. Between 34 and 37 weeks of gestation, births occurred. 45.83% were first-time mothers while 54.16% had given birth multiple times. Of the patients, 41.66% had vaginal deliveries and 58.33% had caesarean sections. Conclusions: Anxious obstetricians find twin pregnancies to be a significant issue. While it is impossible to prevent complications in twin pregnancies, they can be effectively controlled and detected at an early stage. Early diagnosis and prompt treatment of pre-eclampsia and nutritional anemia are necessary to prevent additional complications. Hence, to ensure a more favourable result, increased obstetric care, neonatal care, and health services are needed.